Geology and geochemistry of Bois River Suite, Mara Rosa (GO): evidence of magmatic arc paleoproterozoic - Abdallah, Said (Geochimica Brasiliensis, 2014)
The Bois River Headwaters Suite of, Rosa Mara-Nova Iguaçu (Goiás, Brazil) region, are granitoids to granodioritic and tonalitic with peraluminous characteristics, as distinguished granodiorite VI, granodiorite MU and tonalite SJ, which host gold occurrences. Under the aspect of regional geology, these bodies are intrusive in Santa Terezinha Sequence, and correlate regionally through petrographic and geochemical similarities with Aurmina Suite. These rocks fall into a system collisional to post-collisional, possibly related to the evolution of the magmatic arc paleoproterozoic. Lithogeochemistry showed values in similar reasons MgO/TiO2, suggesting “trend” and evolutive aspect of lower fractionation of elements. In terms of tectonic setting, this suite is calc-alkaline magmatism to crustal contamination or collisional granites type A2, impoverished in Rb and Y. The main changes observed were biotitization, hydrothermal propylitic, sericitic and silicification. Mineral chemical analyzes of biotite and muscovite confirmed distinct generations of these mineral phases, resulting from hydrothermal alteration. The primary biotite, without rebalancing, is composed of series of granites calcium-orogenic alkaline, while the muscovites, more enriched in TiO2, were considered of magmatic origin.